National University Online Radio Using Shoutcast in Radio Laboratory Work Unit: National University Online Radio Using Shoutcast in Radio Laboratory Work Unit - Rafli Ramadhan Gunawan; Septi Andryana; Aris Gunaryati (Jurnal Mantik, 2020)
Today's technological developments, where work can take advantage of existing technologies. Radio is a sound-shaped source of information and nowadays radio has evolved so that it can be accessed through the Internet with streaming media. Streaming radio is not a new technology, but this streaming app is widely implemented by many people. There is a lack of physical radio media among the limited range of broadcasts in an area, limited reach due to weak transmitter frequencies in the area. From the limited range it gives birth to an idea to be able to listen to your favorite radio broadcast anytime and anywhere by utilizing the development of Internet technology as a technique in data compression. In addition, the development of Radio Streaming Media in Indonesia has experienced an increase in which Radio Streaming users from time to time are increasing including application on campus-both public and private campuses. Based on the background that has been outlined, the author will build a Streaming Radio system on the campus of the National University with the Shoutcast method. The results are done by some testers that 93% of online radios can provide up-to-date information, media chats and media requests for listeners and online radios can be accessed well by various users using Internet media via desktop or mobile phone.